A simple but high-performance IM speed drive. (20th May 2009) - Buja, Giuseppe; Menis, Roberto
The paper deals with an induction motor (IM) speed drive having high performance over a large speed range in the constant torque region. The drive is built up around an outer loop of speed equipped with an incremental encoder and two inner loops of torque and flux implemented in a direct torque control (DTC) scheme. The scheme takes advantage of the available speed to estimate the motor torque and the stator flux magnitude by means of the IM current model. This allows the full exploitation of the drive capabilities even in the low speed range. Furthermore, with a suitable representation of the IM current model, the drive can be operated down up to zero speed. The paper closes by analytically investigating the detuned behaviour of the scheme due to a rotor time constant mismatch. Experimental results substantiate the low-speed capabilities of the scheme and the findings on its detuned behaviour.